Comparison of The Effectiveness of Training in Effective Teaching Strategies and A Behavior Management Program on The Self-Concept of Students with Attention-Deficit/Hyperactivity Disorder - Rahmani, Mozhgan; Heydari, Shaban; Salim Bahrami, Seyedeh Hamideh (KMAN Counseling & Psychology Nexus, 2026)
Children with attention-deficit/hyperactivity disorder (ADHD) experience difficulties with their families and teachers, and these weaknesses expose them to many academic problems. Therefore, the present study was conducted with the aim of comparatively examining the effectiveness of educational strategies and behavior management programs on the self-concept of students with ADHD in Miandoroud County. The present study was a semi-experimental research with a pretest–posttest design. The statistical population consisted of all primary school students with ADHD. The Piers–Harris Children’s Self-Concept Scale (1963) was used. A sample of 45 students was selected through multi-stage cluster random sampling and assigned to three groups of 15. The first experimental group received an educational intervention on effective teaching strategies, the second group received training in behavior management, and finally all three groups completed the posttest. The group training sessions on effective teaching methods and behavior management were held over 6 weeks, 60 minutes per day. Descriptive statistics (indices of central tendency and dispersion) and mixed-design repeated-measures analysis of variance, while observing statistical assumptions, were used to test the hypotheses. The data were analyzed using SPSS-26 software. The results of this study showed that both approaches—effective teaching strategies and the behavior management program—had a significant effect on the students’ self-concept, with an eta coefficient of 0.56 (P